2002
DOI: 10.1063/1.1518474
|View full text |Cite
|
Sign up to set email alerts
|

Models for the pedestal temperature at the edge of H-mode tokamak plasmas

Abstract: Predictive models are developed for the temperature at the top at the edge of type 1 ELMy (edge localized mode) H-mode (high-confinement mode) plasmas. Theory-motivated models are used for the pedestal width and pressure gradient, while the pedestal density is obtained from experimental data in this study. The pedestal pressure gradient is assumed to be limited by the ballooning mode instability and is expressed in terms of the magnetic shear and geometrical factors. The effect of the bootstrap current, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
119
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(120 citation statements)
references
References 20 publications
1
119
0
Order By: Relevance
“…30 The width of the pedestal w ped is determined using a mix of magnetic shear and flow shear and can be expressed as…”
Section: Edge Pedestal Temperature and Widthmentioning
confidence: 99%
“…30 The width of the pedestal w ped is determined using a mix of magnetic shear and flow shear and can be expressed as…”
Section: Edge Pedestal Temperature and Widthmentioning
confidence: 99%
“…plasma current I P , toroidal field B T , and input power P in ). Pedestal scaling laws are sought in experimental data on existing tokamaks [9] [10] [11] [12], and attempts have been made to extrapolate current pedestal results to ITER [13]. However, without accurate physics-based pedestal models to help explain experimental results, predictions will always lack certainty.…”
Section: Introductionmentioning
confidence: 99%
“…In the model for pedestal temperature, it is assumed that the edge pressure gradient is limited by high-n ideal MHD ballooning modes and the pedestal width scales like the major radius times the square root of poloidal beta, A = Rdp, [5]. The magnetic shear that is used in the ballooning mode limit is computed one pedestal width from the separatrix and is reduced by the effect of the bootstrap current.…”
mentioning
confidence: 99%
“…The first pedestal model in Ref. [5], which is similar to the one described in this paper, has been used to provide the boundary conditions in simulations of H-mode discharges using the MM95 model in the BALDUR code. It is found that the overall agreement between the modeled profiles and experimental data using the pedestal model previously described is approximately lo%, which is nearly the same as the results obtained when the boundary conditions are prescribed using experimental data.…”
mentioning
confidence: 99%